Effectiveness Of Modern Dressing In Diabetic Ulcer: Case Study - Riyanti, Evy; Frisca, Sanny; Nurjanah, Vausta (UKMC International Conference (UKMC IC) Proceedings, 2024)
Diabetic ulcer wound care has changed from conventional to modern wound care based on the principle of moist balance. Modern dressing can heal diabetic foot ulcers faster and inexpensive. This research conduct effectiveness of modern dressing in diabetic ulcer. This study used dressing that contain hydrogel, chitosan and zinc oxide. Each diabetic patient given three times wound care, once every day for three day and evaluate with Bates-Jansen Wound Assessment before and after intervention. The results is each patient reduces scores in the BWAT assessment from 46 to 37 in first patient, 52 to 48 in second patient and 37 to 30 in third patient. Based on results using modern dressing methods proven reduce ulcer size in each patient, ease pain, less exudate, and reduce inflammation signs. This method can be used for further research by combine more than one type of primary dressing, manage blood glucose by diet and medication program, and involve family in wound care.